Single Atom Array Mimic on Ultrathin MOF Nanosheets Boosts the Safety and Life of Lithium–Sulfur Batteries. Issue 8 (19th January 2020) - Li, Yiju; Lin, Shuangyan; Wang, Dandan; Gao, Tingting; Song, Jianwei; Zhou, Peng; Xu, Zhikun; Yang, Zhenghao; Xiao, Ni; Guo, Shaojun
Abstract: The development of Li–S batteries is largely impeded by the growth of Li dendrites and polysulfide shuttling. To solve these two problems simultaneously, herein the study reports a "single atom array mimic" on ultrathin metal organic framework (MOF) nanosheet‐based bifunctional separator for achieving the highly safe and long life Li–S batteries. In the designed separator, the periodically arranged cobalt atoms coordinated with oxygen atoms (CoO4 moieties) exposed on the surface of ultrathin MOF nanosheets, "single atom array mimic", can greatly homogenize Li ion flux through the strong Li ion adsorption with O atoms at the interface between anode and separator, leading to stable Li striping/plating. Meantime, at the cathode side, the Co single atom array mimic serves as "traps" to suppress polysulfide shuttling by Lewis acid‐base interaction. As a result, the Li–S coin cells with the bifunctional separator exhibit a long cycle life with an ultralow capacity decay of 0.07% per cycle over 600 cycles. Even with a high sulfur loading of 7.8 mg cm −2, an areal capacity of 5.0 mAh cm −2 can be remained after 200 cycles. Moreover, the assembled Li–S pouch cell displays stable cycling performance under various bending angles, demonstrating the potential for practical applications. Abstract : A "single atom array mimic" on ultrathin metal–organic framework (MOF) nanosheets can be utilized in a bifunctional separator to simultaneously suppress the growth of Li dendrites and alleviate polysulfide shuttling. The assembled lithium–sulfur (Li–S) batteries with a bifunctional separator display high specific capacity and long‐term cyclic stability.